CLASSROOM INTERACTION ANALYSIS IN BILINGUAL SCIENCE CLASSES IN SMAN 4 DENPASAR - Kumpul, I Nengah (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2012)
ABSTRACT This study aimed at investigating the classroom interaction types in RSBI class by using FIAC (Flanders Interaction Analysis Categories) system. FIAC system is a system that aims to measure the classroom interaction which has 10 categories, namely (1) accepting feeling, (2) praising and encouraging, (3) accepting or using ideas of student, (4) asking questions, (5) lecturing, (6) giving directions, (7) criticizing or justifying authority, (8) student-talk response, (9) student-talk initiation, and (10) silence. This study was conducted in XI. IPA 1 RSBI in SMA Negeri 4 Denpasar which consisted of thirty six students; twenty one were males and fiveteen were females. This study was carried out based on the case or phenomenon of the growth of RSBI school in Denpasar. For this reason, it is supposed that the classroom interaction of RSBI class will be different from the regular ones. The objectives of this study were to find out the classroom interaction characteristics based on the 10 Flanders categories and to find out the constraints faced by teacher and students in conducting teaching- learning process.   Key words: classroom interaction, Flanders interaction analysis, RSBI class.